Microscale and Molecular Assessment of Impacts of Nickel, Nutrients, and Oxygen Level on Structure and Function of River Biofilm Communities - Lawrence, J. R. (American Society for Microbiology, 2004)
Studies were carried out to assess the influence of nutrients, dissolved oxygen (DO) concentration, and nickel (Ni) on river biofilm development, structure, function, and community composition. Biofilms were cultivated in rotating annular reactors with river water at a DO concentration of 0.5 or 7.5 mg liter(−1), with or without a combination of carbon, nitrogen, and phosphorus (CNP) and with or without Ni at 0.5 mg liter(−1). The effects of Ni were apparent in the elimination of cyanobacterial populations and reduced photosynthetic biomass in the biofilm. Application of lectin-binding analyses indicated changes in exopolymer abundance and a shift in the glycoconjugate makeup of the biofilms, as well as in the response to all treatments. Application of the fluorescent live-dead staining (BacLight Live-Dead staining kit; Molecular Probes, Eugene, Oreg.) indicated an increase in the ratio of live to dead cells under low-oxygen conditions. Nickel treatments had 50 to 75% fewer ‘live’ cells than their corresponding controls. Nickel at 0.5 mg liter(−1) corresponding to the industrial release rate concentration for nickel resulted in reductions in carbon utilization spectra relative to control and CNP treatments without nickel. In these cases, the presence of nickel eliminated the positive influence of nutrients on the biofilm. Other culture-dependent analyses (plate counts and most probable number) revealed no significant treatment effect on the biofilm communities. In the presence of CNP and at both DO levels, Ni negatively affected denitrification but had no effect on hexadecane mineralization or sulfate reduction. Analysis of total community DNA indicated abundant eubacterial 16S ribosomal DNA (rDNA), whereas Archaea were not detected. Amplification of the alkB gene indicated a positive effect of CNP and a negative effect of Ni. The nirS gene was not detected in samples treated with Ni at 0.5 mg liter(−1), indicating a negative effect on specific populations of bacteria, such as denitrifiers, resulting in a reduction in diversity. Denaturing gradient gel electrophoresis revealed that CNP had a beneficial impact on biofilm bacterial diversity at high DO concentrations, but none at low DO concentrations, and that the negative effect of Ni on diversity was similar at both DO concentrations. Notably, Ni resulted in the appearance of unique bands in 16S rDNA from Ni, DO, and CNP treatments. Sequencing results confirmed that the bands belonged to bacteria originating from freshwater and marine environments or from agricultural soils and industrial effluents. The observations indicate that significant interactions occur between Ni, oxygen, and nutrients and that Ni at 0.5 mg liter(−1) may have significant impacts on river microbial community diversity and function.